First principles study of the stability and thermal conductivity of novel Li-Be hybrid ceramics. (15th August 2021) - Samolyuk, G.D.; Edmondson, P.D.
Abstract: Hybrid Li-Be ceramics, combining both tritium (T) breeder (Li) and neutron multiplier (Be) for use as part of the fuel cycle of future nuclear fusion reactors are proposed. The development of such hybrid materials may reduce thermal gradients through better matching of thermal properties, mitigating the detrimental effects that may accompany traditional breeder systems while maintaining acceptable neutron multiplication and T breeding. First-principles methods are used to investigate stability and thermal transport properties of a set of compounds containing both Li and Be. It is demonstrated that BeLi2 O4 Ge and BeLi2 O4 Si are mechanically stable and have formation energies comparable with leading candidates for solid state breeder materials, Li2 TiO3, Li2 ZrO3 . It is also demonstrated that similar to the leading candidates, these compounds are insulators with thermal transport defined by phonons. The calculated thermal conductivity of BeLi2 O4 Ge is slightly higher compared to Li2 TiO3 or Li2 ZrO3 while in the BeLi2 O4 Si it is almost three times higher compared to the rest of compounds due to a higher phonon group velocities and increased phonon lifetimes. These results indicate that hybrid Li-Be ceramics offer a potential route towards better matching of thermal properties with minimal functional property degradation, thereby offering better overall fuel cycle performance. Graphical abstract: Image, graphical abstract